(untitled) (Journal of Architectural Design, 2023)
In the article, on the example of the city of Fergana, the construction processes of cheap and high-quality residential houses in the cities of Uzbekistan were analyzed. Also, the differentiation of medium-sized and multi-storey residential buildings by series was shown